"آليـــــات تحقيـــــــق الشمـــول المـالــــي في الجــــزائـــــر (دراســة حالــة بريـد الجزائــر في توقـــرت) " - حسام, العايب; محمد البشير, مناعي; محمود, بوشاشي (جامعة الوادي - University of Eloued, 2023)
"تهدف الدراسة إلى محاولة معرفة كيف ساهمت وسائل الدفع الحديثة الخاصة ببريد الجزائر في تحقيق وتعزيز الشمول المالي من خلال مؤشراته خاصة في ظل جائحة كورونا كوفيد 19، ولقد تمت الدراسة في بريد الجزائر بولاية توقرت من خلال الإحصائيات المقدمة لنا من مصلحة المالية والنقدية من سنة 2022 الى غاية شهر مارس من سنة 2023 كونها ولاية مستحدثة وخلصت الدراسة إلى أن: 01- زيادة في عدد الصرافات الالية لبريد الجزائر يعزز الشمول المالي. 02- سهولة إستعمال بطاقات الدفع الحديثة منها البطاقة الذهبية وتطبيق بريدي موب يعززان الشمول المالي من خلال زيادة عدد البطاقات والمشتركين من خلال جلب زبائن جدد. ""Summary: The study aims to try to find out how modern payment methods for Algeria Post contributed to achieving and enhancing financial inclusion through its indicators, especially in light of the Corona Covid 19 pandemic. The end of March of the year 2023, as it is a new state, and the study concluded that: 01- An increase in the number of automatic teller machines for Algeria Post, which enhances financial inclusion. 02- Ease of use of modern payment cards, including the golden card and the postal mob application, which enhance financial inclusion by increasing the number of cards and subscribers by bringing in new customers. Keywords: modern means of payment, financial inclusion, Algeria Post, Golden Card and Post Mob. "
Keywords: وسائل الدفع الحديثة، الشمول المالي، بريد الجزائر، بطاقة الذهبية وبريدي موب.; modern means of payment, financial inclusion, Algeria Post, Golden Card and Post Mob.